Effect of Social Media on Purchasing Habits of Consumers in Kathmandu Valley - Prajapati, Trishna (Nepalese Journal of Management, 2024)
This study examines the effect of social media in purchasing habits of consumers in Kathmandu Valley. Consumer purchasing habit is the dependent variable. The selected independent variables are online reviews, advertisement in social media, entertainment marketing, consumer’s satisfaction and trust, social imaging and information search. The primary source of data is used to assess the opinions of the respondents regarding consumer’s purchasing habits through social media in Kathmandu Valley. The study is based on consumers inside Kathmandu Valley with 132 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of in purchasing habits of online reviews, advertisement in social media, entertainment marketing, consumer’s satisfaction and trust, social imaging and information search on consumers purchasing habits in Kathmandu Valley. The study showed that the online review has a positive impact on purchasing habits of consumers. It indicates that positive reviews of the products in social media stimulates the consumer’s purchasing habits. Likewise, the advertisement in social medias is has a positive impact on purchasing habits of consumers. It indicates that advertising through different social media stimulates the purchasing habits of the consumer. In addition, entertainment marketing has a positive impact on purchasing habits of consumers. It indicates that entertainment marketing in social media impulse the purchasing habits of consumers. Further, customer’s satisfaction and trust has a positively impact on purchasing habits of consumers. It indicates that maintaining customer’s satisfaction and trust stimulates the purchasing habits of consumers. Furthermore, social imaging has a positive impact on consumer’s purchasing habits. It indicates that good social imaging of the company drives the consumer’s purchasing habit. The study also revealed that information search has a positive impact on purchasing habits of consumers. It implies that availability of information about the products in social media impulse the purchasing habits of consumer in Kathmandu Valley.